Study of various characteristics of same erysipelothrix rhusiopathiae strains isolated from diseased swines - ΞΕΝΟΣ, Γ.; ΛΑΣΠΙΔΗΣ, XP. (Journal of the Hellenic Veterinary Medical Society, 2019)
At 20 strains of E. rhusiopathiae isolated from acute cases of the disease in swine, the biochemical reactions, the sensitivity to antibiotics and the pathogenic effect to experimental animals were studied. Furthermore it was determined the serotyping of the above strains. The results of this investigation pointed out that: The biochemical reactions of the strains did not appear to have significant deviation from the normal caracteristics of the species. They showed a pronounced sensitivity to tylosin, gentamycin and ampicilline, but some strains were resistant to kanamycin, erythrocine, chloramphenicol and Oxytetracycline too. All the above tested strains were found to be pathogenic to white mice (b.w.20 g), even in a dose of 5X105 orgs/ml. All the 20 strains belongend to serotype A,.